PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP MOTIVASI BERPRESTASI ANTAR ANGGOTA SANGGAR TARI GLOSSY DANCER PEKANBARU - Mega Rizkha Safira; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Effective interpersonal communication is exchanging information, ideas, beliefs, feelings and attitudes between two people whose results are in line with expectations. Achievement motivation is an encouragement and strength in a person to do certain goals that he wants to achieve. In one application, interpersonal communication is used in the field of dance. The main reason for conducting interpersonal communication research on achievement motivation among members of the Pekanbaru Glossy Dancer Dance Studio is because the nature and character between people is different so the way to motivate it is also different. This study uses the Self Disclousure Theory, which is a process of revealing information about yourself to others. Correct interpersonal communication is thought to increase achievement motivation among dance studio members because it is done individually so that members are more open in expressing opinions to other fellow dancers. So the purpose of this study was to determine the magnitude of the influence of interpersonal communication on achievement motivation among members of the Pekanbaru Glossy Dancer Dance Studio. This research is quantitative research using simple linear regression analysis. The independent variable in this study is interpersonal communication, while the dependent variable is achievement motivation. The population in this research is 35 members of the Glossy Dancer Pekanbaru. Sampling is using a non probability sample with a saturated sample method. The technique of collecting data using a questionnaire. The feasibility test of each instrument uses validity and reliability tests. Meanwhile, for processing data using the SPSS Windows version 20.0 program. Based on the results of data processing, the regression coefficient value is Y = 0.761 + 0.734X, with a significance level of 0.000 which is less than 0.05, meaning that interpersonal communication has a major influence on achievement motivation among members of the Pekanbaru Glossy Dancer dance studio. The magnitude of the influence of interpersonal communication on achievement motivation is 56.6% and the remaining 43.4% is influenced by other variables not included in the study.